Potential of waste flowers used as feed additive on the performance of goat kids - WADHWA, M; BAKSHI, M P S (The Indian Journal of Animal Sciences, 2021)
The present study was conducted to assess the impact of temple waste flowers as feed additive on the growth of goat kids. Marigold (Calendula officinalis) flowers constituted the bulk of WFs with negligible red roses (Rosa indica L). Marigold flowers as compared to rose flowers contained high (P<0.01) total phenols and flavonoids; and low (P<0.01) anthocyanins, saponins and vitamin C content. The in vitro studies revealed that the supplementation of WFs at 3 and 5% improved (P<0.01) digestibility of nutrients and VFAs production as compared to control. NGP at tÂ½ increased (P<0.05) linearly up to 4% WFs supplementation and methane production decreased (P<0.05) at all levels of supplementation. Fifteen Beetal goat kids divided into three equal groups were fed TMR, or TMR supplemented with WFs at 3 or 5% of DM intake for 90 days. The daily DM consumed by the animals was similar in all the groups. The digestibility of proximate constituents at 3% level of WF was comparable with control TMR, but depressed (P<0.05) at 5% level of supplementation. The digestibility of cell wall constituents and N retention were not affected by WF supplementation. The average daily gain in weight was improved considerably. It was concluded that bio-active compounds present in WFs reduced the methane emission, resulting in improvement in nutrient utilization and growth of goat kids.